2018
DOI: 10.1186/s12894-018-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of treatment persistence and adherence to mirabegron versus antimuscarinics, for the treatment of overactive bladder in Spain

Abstract: BackgroundPersistence on-treatment with antimuscarinics in patients with overactive bladder (OAB) is reported to be sub-optimal. This retrospective, longitudinal, observational cohort study assessed treatment persistence with β3-adrenoceptor agonists (i.e. mirabegron) and antimuscarinics, both classes of OAB pharmacotherapy, in patients with OAB in Spain.MethodsAdults who received mirabegron or an antimuscarinic in routine clinical practice (1 June–31 October 2014), were identified from anonymised prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 48 publications
7
17
2
2
Order By: Relevance
“…We demonstrated that the TTD and 12‐month persistence rates of OAB medication with antimuscarinics and mirabegron were 91 days and 24% and 245 days and 41% ( p < .0001), respectively. These figures are better than those of previous reports that used data from pharmaceutical claims databases, where the TTD and 12‐month persistence rates were reported to be 50–60 days and 17%–20%, respectively, for antimuscarinics and 90–170 days and 24%–38%, respectively, for mirabegron 5,13,14 . However, most patients discontinued the medication within 1 year.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We demonstrated that the TTD and 12‐month persistence rates of OAB medication with antimuscarinics and mirabegron were 91 days and 24% and 245 days and 41% ( p < .0001), respectively. These figures are better than those of previous reports that used data from pharmaceutical claims databases, where the TTD and 12‐month persistence rates were reported to be 50–60 days and 17%–20%, respectively, for antimuscarinics and 90–170 days and 24%–38%, respectively, for mirabegron 5,13,14 . However, most patients discontinued the medication within 1 year.…”
Section: Discussioncontrasting
confidence: 69%
“…These figures are better than those of previous reports that used data from pharmaceutical claims databases, where the TTD and 12-month persistence rates were reported to be 50-60 days and 17%-20%, respectively, for antimuscarinics and 90-170 days and 24%-38%, respectively, for mirabegron. 5,13,14 However, most patients discontinued the medication within 1 year. Wada et al 15 reported a 1-year persistence rate >60% for mirabegron using a retrospective chart review.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the patient number in each group was small, and more than half of the patients had dropped out of the study by the end of the 12‐month follow‐up period. However, the dropout rate of the study was similar to those of several clinical long‐term studies which disclosed low adherence and persistence to solifenacin and mirabegron in OAB patients in real‐world study 3,21,22 . The dropout rate could be as high as 60% ~ 90% during 12‐month follow‐up.…”
Section: Discussionsupporting
confidence: 75%
“…Conversely, the opposite finding was noted in a Japanese urology clinic study, which reported 12‐month persistence rates of 12.2% and 20.1% with mirabegron and solifenacin, respectively 35 . It is important to note, however, that the Japanese urology clinic study was a prospective, randomized trial when the other studies mentioned above were retrospective database analyses, and these differences in study design may partially explain the contradictory results obtained 13‐15,32‐35 . In addition, the differences observed in the Japanese study were not statistically significant, which was possibly due to the relatively small study population of 148 patients 35 .…”
Section: Discussionmentioning
confidence: 80%
“…In agreement with the specific persistence findings mentioned above, previous real‐world analyses conducted in Canada, Japan, Spain, the US, and the UK typically showed that patients treated with mirabegron remained on treatment longer than those treated with antimuscarinics. 13 , 14 , 15 , 32 , 33 , 34 In these previous studies, 12‐month persistence rates of between 14% and 38% were noted for mirabegron, and rates of between 3% and 25% were reported with antimuscarinics. Conversely, the opposite finding was noted in a Japanese urology clinic study, which reported 12‐month persistence rates of 12.2% and 20.1% with mirabegron and solifenacin, respectively.…”
Section: Discussionmentioning
confidence: 88%